Structural modifications induced by an in vitro maturation process in zona pellucida glycoproteins of bovine oocytes. A Raman microspectroscopy analysis. Issue 86 (2nd September 2016) - Rizo, G.; Roldán-Olarte, M.; Miceli, D. C.; Jiménez, L. E.; Álvarez, R. M. S.
Abstract : Raman microspectroscopy is useful for discrimination between immature and in vitro matured bovine oocytes. Modifications in the glycoproteins of the zona pellucida exerted by the maturation methods might influence the process of in vitro production. Abstract : Oocyte quality is a determinant factor in the efficiency of an in vitro production process. Since the first oocyte–sperm interactions take place in the zona pellucida, the evaluation and characterization of this egg external matrix is of vital importance for the success of the in vitro fertilization process in mammals. Here we evaluate the modifications in the glycoproteins of the zona pellucida of bovine oocytes resulting from in vitro maturation. Using Raman microspectroscopy, subtle spectral differences were straightforwardly related to specific structural changes that could be correlated with known ultrastructural and morphological properties of the zona pellucida. We performed a detailed evaluation of features concerning both the protein backbone and the glycan moieties of the glycoproteins of the zona pellucida from immature and in vitro matured oocytes. Specific spectral differences involving amide I, amide III, and several bands belonging to the sugar residues allowed the characterization of these two stages in oocyte maturation. A molecular rearrangement of the glycoproteins consisting in the exposition of terminal sugar residues that play a key role in sperm recognition while the glycan core is covered by the polypeptide chain was derived from this study. These results demonstrate the efficiency of the Raman microspectroscopy technique to perform a biochemical characterization of the zona pellucida of bovine oocytes. This technique would be useful to discriminate between immature and in vitro matured oocytes and could also provide a basis for the understanding of the changes induced by maturation methods and of their impact on in vitro fertilization.